Respostas
respondido por:
1
ax² + bx + c= 0
Exemplo:
2x² + 3x + (-5)=0 ( a = 2 b = 3 c = -5)
2x² + 3x - 5= 0
x= -b (+,-) √Δ
___________
2.a
x= - 3 (+,-)√Δ
__________
2×2
Δ= b² - 4ac
3² - 4.(2). (-5)
Δ=9- [-8 (-5)]
Δ= 9 + 40
Δ= 49
x= -3 (+,-) ²√49
___________
4
x=-3(+,-) 7 x = -3 + 7÷ 4 x= -3 - 7÷ 4
___________ x=4/4 x= -10/4
4 x = 1 x= 2,5
Exemplo:
2x² + 3x + (-5)=0 ( a = 2 b = 3 c = -5)
2x² + 3x - 5= 0
x= -b (+,-) √Δ
___________
2.a
x= - 3 (+,-)√Δ
__________
2×2
Δ= b² - 4ac
3² - 4.(2). (-5)
Δ=9- [-8 (-5)]
Δ= 9 + 40
Δ= 49
x= -3 (+,-) ²√49
___________
4
x=-3(+,-) 7 x = -3 + 7÷ 4 x= -3 - 7÷ 4
___________ x=4/4 x= -10/4
4 x = 1 x= 2,5
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás